PEMBIAYAAN MURABAHAH PERSPEKTIF EKONOMI ISLAM - Rahmad (HEI EMA : Jurnal Riset Hukum, Ekonomi Islam, Ekonomi, Manajemen dan Akuntansi, 2022)
Murabahah is a sale and purchase that is designed to be mutually beneficial but in the future there will be problems due to modifications in the payment system and the involvement of third parties. The higher selling price on credit is solely due to save the seller from the risk of future inflation, although the imposition of a credit price higher than the cash price is still a mistake. Debt in a murabahah transaction is the buyer's obligation that must be fulfilled because it is a right that must be owned by the seller after fulfilling his obligations. Delaying payments not for syar'i reasons is a form of tyranny and pollutes the spirit of murabahah based on Ta’awun